2011
DOI: 10.1038/gt.2011.131
|View full text |Cite|
|
Sign up to set email alerts
|

Suicidal gene therapy in the effective control of primary human hepatocellular carcinoma as monitored by noninvasive bioimaging

Abstract: Hepatocellular carcinoma (HCC) is usually refractory to the available treatments. For cancer gene therapy purposes, real-time imaging of therapeutic gene expression is of great importance because there are multiple factors that modulate the therapeutic gene expression in a complex tumor microenvironment. As a consequence, multiple doses of therapeutic viral vectors may be required for improved efficacy. In the present study, the luciferase reporter gene and the yeast cytosine deaminase (yCD) genes were bicistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…CD also catalyzes, by means of a deamination step, the conversion of the prodrug 5-FC to the chemotherapeutic drug 5-FU 9,10 within cancer cells expressing gene therapy-delivered CD. CDbased prodrug activating gene therapy has been investigated in preclinical animal models and clinical trials for many cancer types, including colon, 11,12 liver, 13,14 head and neck, 25,26 sarcomas, 27,28 melanoma, 11,29 and ovarian 13,30 cancers. CD-based cancer gene therapy has proven to be effective in chemotherapyresistant cancer cell lines, 31,32 in combination with chemotherapy, 4 and to enhance the effect of radiotherapy.…”
mentioning
confidence: 99%
“…CD also catalyzes, by means of a deamination step, the conversion of the prodrug 5-FC to the chemotherapeutic drug 5-FU 9,10 within cancer cells expressing gene therapy-delivered CD. CDbased prodrug activating gene therapy has been investigated in preclinical animal models and clinical trials for many cancer types, including colon, 11,12 liver, 13,14 head and neck, 25,26 sarcomas, 27,28 melanoma, 11,29 and ovarian 13,30 cancers. CD-based cancer gene therapy has proven to be effective in chemotherapyresistant cancer cell lines, 31,32 in combination with chemotherapy, 4 and to enhance the effect of radiotherapy.…”
mentioning
confidence: 99%
“…Until recently, diverse gene therapy strategies for HCC have been examined, such as gene augmentation therapy for tumor suppressor gene [5], drug sensitization therapy including the HSV1-tk/ganciclovir [6,24] or cytosine deaminase/5-fluorocytosine [25], and genetic immunotherapy using a cytokine gene [4]. Also, since the NIS gene was first cloned in 1996 [26], many studies have demonstrated the efficacy of molecular imaging or radioiodide gene therapy using NIS in vitro and in vivo [16,17,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Foka et al, [168] identified and experimentally characterized novel hepatoma-specific promoters, which were valuable for cancer-specific gene therapy, by using HSV-1 vectors. Sia et al, [170] used as a viral vector the HSV-1 amplicon in HCC and non-HCC cell lines in vitro and in vivo with promising results. Several other reports characterized different kinds of HSV-1 vectors as platforms for virotherapy against liver cancer [167,168,[171][172][173].…”
Section: Inhibition Of Oncogenes and Restoration Of Tumor-suppressor mentioning
confidence: 99%